The calcium saga: a matter of life and death - Nicotera, Pierluigi (Henry Stewart Talks, 2007)
Calcium and cytotoxicity, Indicator dyes for calcium detection, Alteration of thiol and calcium homeostasis causes cell death, Oxidative stress and thiol modification impair calcium storage and extrusion, Calcium ATPase, The calcium and thiol hypothesis of cell death, Calcium as a second messenger, Calcium is involved in different cell death paradigms, Nuclear calcium transport, Intracellular calcium distribution, PMCAs: vital membrane calcium transporters, PMCAs are degraded during cell death, Non-degradable PMCAs protect against cell death, Mechanisms of calcium deregulation during cell death, NCX3 and calpains in calcium maintenance, Prevention of excitotoxicity via calcium management
Archived at 2021/02/25